2014
DOI: 10.1049/el.2013.3175
|View full text |Cite
|
Sign up to set email alerts
|

Resistive switching behaviour in ZnO and VO 2 memristors grown by pulsed laser deposition

Abstract: The resistive switching behaviour observed in micro scale memristors based on laser ablated ZnO and VO2 is reported. A comparison between the two materials is reported against an active device size. The results show that devices up to 300 × 300 μm2 exhibit a memristive behaviour regardless of the device size, and 100 × 100 μm2 ZnO-based memristors have the best resistance off/on ratio

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 7 publications
0
19
0
1
Order By: Relevance
“…In the work presented herein, we obtained the full Cu 2 O/AZO/ZnO stack structure after a unique three-step pulsed laser deposition (PLD) process, [24][25][26][27][28][29] making the fabrication process simpler and decreasing the damage compared with other literature reports 18-23 and further improving the quality of the heterojunction in terms of the interface, surface roughness, passivation, and leakage currents. Study of the morphological, structural, optical, and electrical properties of the deposited Cu 2 O/AZO and Cu 2 O/ZnO/AZO heterojunctions revealed that the p-Cu 2 O/n-ZnO/n-AZO heterojunctions exhibited well-defined rectifying behavior and could thus be useful for future high-performance heterostructure photovoltaic devices.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…In the work presented herein, we obtained the full Cu 2 O/AZO/ZnO stack structure after a unique three-step pulsed laser deposition (PLD) process, [24][25][26][27][28][29] making the fabrication process simpler and decreasing the damage compared with other literature reports 18-23 and further improving the quality of the heterojunction in terms of the interface, surface roughness, passivation, and leakage currents. Study of the morphological, structural, optical, and electrical properties of the deposited Cu 2 O/AZO and Cu 2 O/ZnO/AZO heterojunctions revealed that the p-Cu 2 O/n-ZnO/n-AZO heterojunctions exhibited well-defined rectifying behavior and could thus be useful for future high-performance heterostructure photovoltaic devices.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…[1] The major disadvantage of 3D crossbars currently is the high-leakage or sneak-path current. [3] Depending on the stoichiometry, crystal structure, and device structure it has demonstrated bipolar resistive switching (BRS) [4][5][6][7][8][9][10] as well as apolar threshold switching (TS). [3] Depending on the stoichiometry, crystal structure, and device structure it has demonstrated bipolar resistive switching (BRS) [4][5][6][7][8][9][10] as well as apolar threshold switching (TS).…”
mentioning
confidence: 99%
“…10 In contrast, VO x thin films have also been reported recently for resistive switching performance by several groups. [11][12][13][14] However, application of VO x 2D nanosheets in resistive switching memory devices is not yet reported. Hence, it is important to study the resistive switching property of this important 2D oxide in details.…”
mentioning
confidence: 99%